2022
DOI: 10.7748/ldp.2021.e2166
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the mental health needs of a young person with an intellectual disability: a case study

Abstract: Young people with intellectual disabilities are at greater risk of developing mental health issues. However, their mental health needs are often not recognised and therefore remain untreated. This article discusses a case study concerning a young man whose mental health needs were first noted in adolescence, and describes his experiences of accessing appropriate services and interventions. Community-based services have provided treatment and support, enabling him to continue living with his family.The case stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The results of a survey from 2001 found those aged 5-15 at an overall OCD prevalence of 0.25% [ 3 ]. Furthermore, it revealed that OCD rarely presents in young children; however, the onset of symptoms is generally during adolescence [ 3 , 4 ]. Diagnosing is further challenged by the difficulty of assessing obsessions with varying genetic risk factors and pediatric presentations.…”
Section: Introduction (Background)mentioning
confidence: 99%
“…The results of a survey from 2001 found those aged 5-15 at an overall OCD prevalence of 0.25% [ 3 ]. Furthermore, it revealed that OCD rarely presents in young children; however, the onset of symptoms is generally during adolescence [ 3 , 4 ]. Diagnosing is further challenged by the difficulty of assessing obsessions with varying genetic risk factors and pediatric presentations.…”
Section: Introduction (Background)mentioning
confidence: 99%